2006
DOI: 10.1002/jnr.20956
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of brain‐derived neurotrophic factor in BDNF+/− mice is associated with enhanced recovery of motor performance and increased neuroblast number following experimental stroke

Abstract: Brain-derived neurotrophic factor (BDNF) is involved in brain plasticity and neuronal survival. Generally, BDNF enhances synaptic activity and neurite growth, although the effect of BDNF on neuronal survival and brain plasticity following injury is equivocal. Housing rats in an enriched environment after experimental stroke enhances recovery of sensory-motor function, which is associated with a decrease in the BDNF mRNA and protein levels. We used BDNF(+/-) mice and wild-type littermate mice to investigate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 41 publications
4
17
1
2
Order By: Relevance
“…It was also shown that BDNF might increase angiogenesis and behavioral recovery in mouse intracranial hemorrhage model (Lee et al, 2010), the same as in mouse ischemic stroke model (Qin et al, 2011). In our study BDNF −196 G>A polymorphism was not found to have any impact on human ischemic stroke within short-term observation, but some animal studies also argue against beneficial effect of BDNF in the model of cerebral ischemia (Gustafsson et al, 2003;Nygren et al, 2006).…”
Section: Discussionsupporting
confidence: 37%
“…It was also shown that BDNF might increase angiogenesis and behavioral recovery in mouse intracranial hemorrhage model (Lee et al, 2010), the same as in mouse ischemic stroke model (Qin et al, 2011). In our study BDNF −196 G>A polymorphism was not found to have any impact on human ischemic stroke within short-term observation, but some animal studies also argue against beneficial effect of BDNF in the model of cerebral ischemia (Gustafsson et al, 2003;Nygren et al, 2006).…”
Section: Discussionsupporting
confidence: 37%
“…17 Alternatively, inhibiting BDNF appears to have the potential to attenuate recovery processes. 18 Recent findings show that healthy individuals with a val66met polymorphism in the BDNF gene show reduced ability to change cortical maps in response to motor training. 19 In addition, blocking BDNF decreases cAMP response-element-binding protein and synapsin 1, which are regulated by BDNF, and this impairs learning and memory.…”
mentioning
confidence: 99%
“…[18,19,29,52,53] Paradoxically, one study conducted in BDNF(+/−) mice showed enhanced functional recovery after stroke with decreased brain levels of BDNF. [54] Ploughman et al assessed the role of endogenous BDNF in rehabilitation induced stroke recovery through knocking down BDNF expression using antisense BDNF oligonucleotide infusion. Their data demonstrated an indispensable role of BDNF in rehabilitation induced recovery after stroke.…”
Section: Discussionmentioning
confidence: 99%